China’s response to a national land-system sustainability emergency - Bryan, Brett A.; Gao, Lei; Ye, Yanqiong; Sun, Xiufeng; Connor, Jeffery D.; Crossman, Neville D.; Stafford-Smith, Mark; Wu, Jianguo; He, Chunyang; Yu, Deyong; Liu, Zhifeng; Li, Ang; et al. (Nature (London), 2018)
China has responded to a national land-system sustainability emergency via an integrated portfolio of large-scale programmes. Here we review 16 sustainability programmes, which invested US$378.5 billion (in 2015 US$), covered 623.9 million hectares of land and involved over 500 million people, mostly since 1998. We find overwhelmingly that the interventions improved the sustainability of China’s rural land systems, but the impacts are nuanced and adverse outcomes have occurred. We identify some key characteristics of programme success, potential risks to their durability, and future research needs. We suggest directions for China and other nations as they progress towards the Sustainable Development Goals of the United Nations’ Agenda 2030. China has addressed widespread rural poverty and environmental degradation head-on via unprecedented investment in sixteen large-scale sustainability programmes.